Integrated cervical cancer screening uptake and associated factors among women attending primary care services at public health centres in Addis Ababa, Ethiopia: a multicentre cross-sectional study - Kassahun Alemu Gelaye; Akinyinka Omigbodun; Rahel Nega Kassa (BMJ Publishing Group, 2024)
Background Cervical cancer (CC) is a major health problem in Ethiopia. Integrated healthcare approaches have been suggested as a way to increase access to and utilisation of screening services. Limited data exists on integrated CC screening (CCS) uptake at the primary care facilities where most women access healthcare. This study aimed to determine integrated CCS uptake and associated factors among women attending primary care services at health centres (HCs) in Addis Ababa, Ethiopia.Methods A multicentred cross-sectional study design was conducted among 1366 women attending primary care services at HCs in Addis Ababa. A systematic random sampling method was used to reach the study participants. Sexually active women aged 30-49 years attending primary care services in HCs were included in the study. A multivariable logistic regression model, with Stata/MP V.17.0 software, was used to identify the factors associated with integrated CCS service utilisation at a p value<0.05. Findings were presented using adjusted OR (AORs) with 95% CI.Result Only 15.6% (95% CI: 13.7 to 17.6) of women used the CCS that was integrated into the primary care services that they initially sought. Being single (AOR: 4.10; 95% CI: 2.19 to 7.68), divorced (AOR: 2.33; 95% CI: 1.04 to 5.21), attending college and above (AOR: 5.86; 95% CI: 2.32 to 14.79), being in the richest wealth index (AOR: 2.76; 95% CI: 1.46 to 5.22), husband's sexual behaviour (AOR: 6.8; 95% CI: 4.09 to 11.21), having a favourable attitude towards CCS (AOR: 2.24; 95% CI: 1.52 to 3.29) and visiting postnatal clinic (AOR: 8.06; 95% CI: 2.33 to 27.8) were associated with utilisation of CCS services, while preference of a specific gender of healthcare provider (HCP) (AOR: 0.04; 95% CI: 0.02 to 0.13) was associated with non-utilisation of CCS.Conclusion The study found low integrated CCS uptake among women in Addis Ababa, influenced by factors like marital status, education, wealth, husband's sexual behaviour, attitude towards CCS, postnatal clinic visits and preferred gender of HCPs. Taking these factors into consideration by stakeholders could promote CCS utilisation.